How deep sea divers use math - Arroyo, Sheri L. (New York : Chelsea Clubhouse, 2010)
Looks at some of the many ways in which deep sea divers use math on a daily basis to determine how long they can stay in cold water, determine how much air is left in an oxygen tank, and more.
What is deep sea diving? -- Scuba diving in the sunlit zone -- How far can I see? -- Diving in the deep -- The pressure is on! -- How deep is the ocean? -- How much air will I need? -- Underwater geologists -- Exploring shipwrecks -- Marine biology -- Diving for the navy -- Antarctic research -- If you want to be a deep sea diver.
Includes bibliographical references (p. 31) and index.
6.4
3-6
3-6
Keywords: Deep diving -- Mathematics -- Juvenile literature; Mathematics -- Juvenile literature; Scuba divers -- Juvenile literature; Scuba diving -- Mathematics -- Juvenile literature; Deep diving -- Mathematics; Mathematics; Scuba divers; Scuba diving -- Mathematics; Deep diving -- Mathematics; Mathematics; Scuba divers; Scuba diving -- Mathematics